Environmental management in Brazil: A survey evaluating current practice and performance in the industrial sector - Wagner Cezar Lucato; Rosângela Maria Vanalle; Milton Vieira Júnior; José Carlos da Silva Santos (African Journal of Environmental Economics and Management, 2013)
The rapid urban development observed in major cities and the resulting environmental impacts have made the lessening of these impacts a key objective in sustainable development and companies have been required to consider economic, environmental and social consequences in their cultures, strategies and decision-making processes. The goal of this paper was to evaluate to what extent manufacturing companies have been responding to these challenges. The study was performed with a survey that considered 63 manufacturing firms of different sizes and from a variety of sectors located in Brazil. The results of the research and the statistical analysis performed on these results suggested that the actions taken by industries to face their environmental challenges have generally been effective and surpassed the environmental demands enforced by the law in multiple ways. The hypotheses tested as part of this experiment allowed the researchers to verify that companies with ISO 14001 certification had better environmental performance than those without it, as expected. It was also possible to verify that the discipline imposed by forms of certification other than ISO 14001 have had positive influence on the environmental performance. The research results confirmed that multinational companies had better environmental performance than Brazilian national firms. On the other hand, firm size did matter in terms of environmental performance, but no significant difference was perceived among manufacturing companies in different industrial sectors.